THE EFFORTS TO IMPROVE LEARNING ACHIEVEMENT IN NATIONAL REVENUE MATERIALS THROUGH THE IMPLEMENTATION OF THE MIND MAPPING METHOD; CLASS OF XI IPS 2 ODD SEMESTER STUDENTS OF SMA NEGERI 1 TEGALDLIMO BANYUWANGI, ACADEMIC YEAR OF 2020/2021: UPAYA MENINGKATAN PRESTASI BELAJAR MATA PELAJARAN EKONOMI MATERI PENDAPATAN NASIONAL MELALUI PENERAPAN METODE MIND MAPPING PADA SISWA KELAS XI IPS 2 SEMESTER GANJIL SMA NEGERI 1 TEGALDLIMO BANYUWANGI TAHUN PELAJARAN 2020/2021 - Akhlakul Karimah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
This research study aims to improve student achievement, by using the Mind Mapping method in the class of XI IPS 2 on Economics subject, National Income of SMA Negeri 1 Tegaldlimo Banyuwangi. The form of this research is Classroom Action Research (CAR), and the research subject is the students of class XI IPS 2 SMA Negeri 1 Tegaldlimo Banyuwangi, which amounted to 33 students. The results showed that there was a gradual increase where the student learning outcomes from the first cycle were 69.44% and increased in the second cycle by 94.73%. So, the student activity increased by 25.29% in achievement. By the completeness number of 87.36%, where the percentage of 100% classically has increased. So it can be concluded that the use of the Mind Mapping method can improve student achievement outcomes in Economics subject National Income Material, class of XI IPS 2 SMA Negeri 1 Tegaldlimo Banyuwangi Academic Year of 2020/2021.